Maternal satisfaction with delivery services at tertiary university hospital in upper Egypt, is it actually satisfying? - Sayed, Waleed; Abd ElAal, Diaa Eldeen M.; Mohammed, Hazem S.; Abbas, Ahmed M.; Zahran, Kamal M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal health has therefore become an important aspect of policy and planning for healthcare, as reflected by its inclusion as the fifth Millennium Development Goal (MDG). The objective of the present investigation was to determine the maternal satisfaction towards delivery services at Women’s Health Hospital, Assiut University, Upper Egypt Methods: A cross sectional study was performed. The study was conducted during February- April 2016 on a sample of 400 delivering mothers; the data were collected using a semi-structured questionnaire and analyzed by SPSS version21. Statistical tests were used, and significance level was taken at p-value <0.05. Results: A total of 400 delivering mothers were interviewed, of which 67.0 % of the respondents were between the age group of 20-30, 76.75 % were from rural areas, 48.0%were illiterate, 86.75% were house wives and 46.0% belonged to the income group of less than 500 EGP. The findings of the study showed that the overall maternal satisfaction level with the delivery services rendered at the hospital was 78.5%, while 21.5% were dissatisfied. Furthermore, satisfaction with the delivery service was found to have a significant association with the age of the respondents and educational level of the respondents. Moreover, results suggest that women are satisfied with the communication factors, interpersonal behavior, good management, and general satisfaction. Women were least satisfied with privacy sensation during hospital stay and obligatory blood donation. Conclusions: Although most participants were satisfied by the delivery service provided to them during delivery, Dissatisfaction by a minority group resulted in a limited ability of communication with mothers, lack of privacy sensation during hospital stay and obligatory blood donation. Thus, mechanisms should be developed to increase maternal satisfaction in our hospital.